NOTAS SOBRE LA REJERÍA MURCIANA DE LOS SIGLOS XVII Y XVIII - Pérez Sánchez, Manuel (Imafronte, 1995)
The art of grille-work in Murcia offers a number of aspects still to be discovered. Although the important works in churches have been studied in depth, the same cannot be said of the ironwork designed especially for civil buildings. Notable among these are the works produced in the first third of the 17th century, which must be considered the age of splendour for grille-work in Murcia. This was the age of ironsmiths such as Francisco Hernández, Pedro Romero, Ginés García, Andrés Martínez or the Ortigosa family, who gradually introduced a refined classical aestheticism to Murcia, with the consequent abandonment of the earlier ornamental styles. The 18th century is also an interesting, although undervalued, period in this field, as testified by the fine examples of grille-work decorating palaces and houses in the city of Murcia and churches such as Murcia Cathedral and Santa María de Gracia in Cartagena, where interesting examples of Rococo grille-work are to be found.